2013
DOI: 10.1136/heartjnl-2012-303151
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab-induced cardiotoxicity in early breast cancer patients: a retrospective study of possible risk and protective factors

Abstract: TIC is a frequent, albeit generally mild, adverse event in clinical practice. Further studies are warranted to better define the risk of and protective factors for TIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 29 publications
1
73
1
5
Order By: Relevance
“…Past use of anthracyclines, especially at high cumulative doses (>250 mg/m 2 of doxorubicin or >600 mg/m 2 of epirubicin),53 appears to be the most important risk factor for subsequent cardiac dysfunction 49. In 1 retrospective analysis, past anthracycline use was the only significant predictor of trastuzumab‐induced cardiotoxicity 54. Additionally, concomitant use of anthracycline or short period (3 weeks versus 3 months) between anthracycline use and administration of trastuzumab appear to increase the risk of cardiac adverse events in some studies 14, 55.…”
Section: Risk Factors For Cardiotoxicity Associated With Her2 Targetementioning
confidence: 99%
“…Past use of anthracyclines, especially at high cumulative doses (>250 mg/m 2 of doxorubicin or >600 mg/m 2 of epirubicin),53 appears to be the most important risk factor for subsequent cardiac dysfunction 49. In 1 retrospective analysis, past anthracycline use was the only significant predictor of trastuzumab‐induced cardiotoxicity 54. Additionally, concomitant use of anthracycline or short period (3 weeks versus 3 months) between anthracycline use and administration of trastuzumab appear to increase the risk of cardiac adverse events in some studies 14, 55.…”
Section: Risk Factors For Cardiotoxicity Associated With Her2 Targetementioning
confidence: 99%
“…It did not include patients with reduced cardiac function at baseline and identified coronary artery disease, atrial fibrillation, hypertension, diabetes mellitus, chronic kidney disease, aged >74 years, and administration of other chemotherapy as risk factors 28. Other retrospective cohort studies, not limited to a Medicare population but including patients of all ages, were unable to identify any predictors for TIC other than >240 mg/m 2 doxorubicin exposure 9, 29. However, this has also not been consistently seen as a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the HERA (HERceptin Adjuvant) trial showed an HF incidence of only 0.8% and decreases in LVEF of ≥10% from baseline to an LVEF of <50% in only 7.2% of patients 34. In contrast, real world cohort studies noted a decline in LVEF by ≥10% points in 15% to 40% of patients 9, 29. The current study is in agreement with these previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been seen that cardiac side-effects may occur after adjuvant treatment with trastuzumab, with an absolute 12.0% higher adjusted incidence rate for heart failure over 3 years (2). Although preclinical data originally pointed towards a radiosensitizing effect of trastuzumab, more recent clinical studies have demonstrated that concurrent RT and trastuzumab for EBC is not associated with increased acute adverse events, including those of a cardiological nature (3,4).…”
mentioning
confidence: 99%